2016
DOI: 10.1371/journal.pone.0154969
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Non-Medical Characteristics Contribute to Collective Medical Decision-Making at Multidisciplinary Oncological Team Meetings

Abstract: BackgroundThe contribution of patients’ non-medical characteristics to individual physicians’ decision-making has attracted considerable attention, but little information is available on this topic in the context of collective decision-making. Medical decision-making at cancer centres is currently carried out using a collective approach, at MultiDisciplinary Team (MDT) meetings. The aim of this study was to determine how patients’ non-medical characteristics are presented at MDT meetings and how this informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(27 reference statements)
5
23
0
Order By: Relevance
“…The number of case discussions, mean 12.6 (range 2-36), the length of the meetings, mean 0.88 h, and the time per case discussion, mean 4.2 min. were also comparable to observations from UK with 14-35 case discussions, MDTM lengths of 1-2.5 h and case discussions of 4-7 min [13,14]. MDTM length naturally correlates with the number of case discussions, but also other factors such as cancer type, hospital type, use of video facilities influence MDTM length (Figure 1).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The number of case discussions, mean 12.6 (range 2-36), the length of the meetings, mean 0.88 h, and the time per case discussion, mean 4.2 min. were also comparable to observations from UK with 14-35 case discussions, MDTM lengths of 1-2.5 h and case discussions of 4-7 min [13,14]. MDTM length naturally correlates with the number of case discussions, but also other factors such as cancer type, hospital type, use of video facilities influence MDTM length (Figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…In cancer care, MDTMs represent an important possibility for case review and expert opinion. Based on observations and time estimates from cancer-related MDTM in Swedish health care we demonstrate that mean 8.2 physicians and 2.9 nurses-coordinators participate in the MDTMs, which is in line with data from UK on 6-10 participating physicians [13]. The number of case discussions, mean 12.6 (range 2-36), the length of the meetings, mean 0.88 h, and the time per case discussion, mean 4.2 min.…”
Section: Discussionsupporting
confidence: 83%
“…Though many MDTM groups struggle with how to best include patient-related perspective in the decision process, a limited focus on these aspects have been documented in several studies [ 21 ]. Restivo et al found that psychological, socio-demographic and relational aspects were discussed in 30% of the cases and patient’ preferences were discussed in 10% of the cases at MDTMs in French health care [ 22 ]. Divergent treatment priorities between physicians and patients have been demonstrated in multiple studies and cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…MDTM leaders often express a clear view on the optimal treatment recommendation. Team members may counteract this by providing additional patient-related information, which may influence the further discussion, though perhaps based on fragmented and selected information [ 22 ]. Additionally, when the information is conveyed to the patient, it needs to be balanced, which requires that controversies and differences in opinion have been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…33 Another observational study of tumour board meetings showed that patient characteristics were mentioned more frequently during those meetings where more time was spent discussing an individual patient. 32 The current study setup is not designed to show such causalities. In the light of these previous study results, however, it is plausible that the way patient workup was organised might be limiting the proper use of SDM principles.…”
Section: Statement Of Principal Findingsmentioning
confidence: 99%